Mechanisms of corticosteroid action on lymphocyte subpopulations. III. Differential effects of dexamethasone administration on subpopulations of effector cells mediating cellular cytotoxicity in man - Parrillo, J. E. (1978)
The present study investigated the effect of dexamethasone (DEX) administration on different populations of mononuclear cells and neutrophils mediating antibody-dependent cellular cytotoxicity (ADCC) against different target cells. Mononuclear cells (lymphocytes and monocytes) and neutrophils were obtained from twenty-seven normal volunteers at 0, 4, 24 and 48 hr after oral administration of 21 mg of DEX. ADCC was determined utilizing the following targets: human red blood cells (HRBC), Chang liver cells (Ch) and human heart cells (HHC). The predominant mononuclear effector in HRBC killing was shown to be a monocyte and in Ch and HHC killing, a K cell. As previously shown, DEX produced a profound monocytopenia and lymphocytopenia at 4 hr with a return of lymphocyte counts to normal and monocyte counts to supra-normal at 24 hr. At the point of maximal monocytopenia, monocyte-mediated HRBC killing decreased from a geometric mean of 14 to 4 lytic units per 10(8) effector cells (P<0·05) and rebounded at 24 hr to a mean of 39 lytic units (P<0·02) with the rebound monocytosis. At the point of absolute lymphopenia (4 hr), there was a relative enrichment in the proportion of lymphocytes bearing an Fc receptor (K cells, P<0·01). Concomitant with this was an increase in ADCC against Ch and HHC from geometric means of 1121 to 7172 lytic units and 939 to 7354 lytic units (P<0·001) respectively. Thus, a major action of DEX administration on mononuclear ADCC was to differentially enrich or deplete different effector cells to and from the circulation, causing changes in cytotoxicity. Since the cytotoxicity paralleled the proportion of effector cells, the cells remaining in the circulation following DEX administration retained normal antibody-dependent cytotoxic capabilities. Neutrophil-mediated ADCC against HRBC significantly increased at 4 hr from a geometric mean of 3785 to 20142 lytic units (P<0·02) concomitant with the blood neutrophilia and remained elevated for 72 hr. Neutrophil ADCC against Ch and HHC was minimal and was not affected by DEX administration. This study demonstrates differential effects of corticosteroids on antibody-dependent cell-mediated cytotoxicity, reflecting changes in proportion of circulating effector cell populations. These changes depend on (a) the target cell employed, (b) the effector cell mediating cytotoxicity and (c) the duration of time since the last dose of corticosteroid.